Pattern of Pediatric Surgical Admissions in a Combined Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Pediatric surgical admissions are daily practice at peripheral hospital. To design strategy for appropriate diagnosis and management of pediatric surgical patient reported to combined military hospital (CMH) Bogura, Bangladesh.Objectives: To find out the pattern of pediatric surgical admission cases and factors affecting their outcomes.Methods: This case series analysis was conducted from November 2016 to October 2017 at CMH, Bogura. Total 175 patients admitted during this period out of them13 children excluded from study due to parent’s refusal for intervention or discharged against medical advice. In this study total 162 admitted children’s data were analyzed.Results: The study showed emergency cases were predominating 74.69% and elective cases were less common 25.30%. Mortality recorded exclusively in children admitted on emergency basis 6 children (3.70%). Congenital anomaly of GIT was found the leading causes of death in this study 4 (2.46%) children.Conclusion: Many emergency and elective pediatric surgical patients can be managed at peripheral Hospital with acceptable outcomes except the neonate.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 109-112